Disentangling practitioners’ understandings of child sexual exploitation: The risks of assuming otherwise? - Weston, Samantha (Criminology & criminal justice, 2022)
This article reports findings from a qualitative study investigating the efficacy and the effects of a child sexual exploitation awareness raising intervention with young people. Drawing on in-depth interviews with members of a multi-agency team set up to prevent child sexual exploitation, we elucidate the way in which practitioners communicate the problem of child sexual exploitation and how risk registers are deployed to assess the dangerousness of young people’s behaviours. In examining practitioners’ understandings of child sexual exploitation, we illuminate the ways in which educative interventions in this domain are informed by a confluence of policy guidelines and personal/experiential perceptions. Unravelling the tensions arising between these two frames of interpretation, we illustrate that – despite routine recourse to embedded professional knowledge – underlying moral and cultural assumptions alongside anxieties about childhood sexuality influence practitioners’ understandings of the nature of risk, who is at risk and the context in which risks manifest themselves.